Stigma among patients with HIV/AIDS: a cross-sectional study in Malaysia - Abdullah, Azreen; Ismail, Adibah Hanim; Mooi, Ching Siew (International Journal of Human and Health Sciences, 2020)
Introduction:HIV stigma refers to negative beliefs, feelings and attitudes towards people living with HIV (PLWH), groups associated with PLWH and other key populations at higher risk of HIV infection, such as people who inject drugs, sex workers, men who have sex with men and transgender people. Despite the advancement made in the knowledge and treatment of HIV, PLWH continues to be stigmatized.